2022
DOI: 10.3389/fphar.2022.889799
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine for Primary Liver Cancer Therapy: Perspectives and Challenges

Abstract: Primary liver cancer (PLC) is one of the most common solid malignancies. However, PLC drug development has been slow, and first-line treatments are still needed; thus, studies exploring and developing alternative strategies for effective PLC treatment are urgently needed. Chinese herbal medicine (CHM) has long been applied in the clinic due to its advantages of low toxicity and targeting of multiple factors and pathways, and it has great potential for the development of novel natural drugs against PLC.Purpose:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 128 publications
0
10
0
Order By: Relevance
“…Many investigations have revealed that our TCM can exert anti-liver cancer effects via regulating several target genes [16,17] . Convincing evidence have presented that miRNAs are abnormally expressed in liver cancer and can regulate tumor development by inhibiting target genes, and may also serve as a potential target for liver cancer therapy [18,19] .…”
Section: Resultsmentioning
confidence: 99%
“…Many investigations have revealed that our TCM can exert anti-liver cancer effects via regulating several target genes [16,17] . Convincing evidence have presented that miRNAs are abnormally expressed in liver cancer and can regulate tumor development by inhibiting target genes, and may also serve as a potential target for liver cancer therapy [18,19] .…”
Section: Resultsmentioning
confidence: 99%
“…The integration of traditional Chinese medicine, drawing on three thousand years of Chinese medical practice, has become a notable approach ( Liu et al, 2019 ; Changou et al, 2021 ; Li K. et al, 2022 ). Huaier granules, classified as proprietary Chinese medicines, offer the advantages of low toxicity and convenient administration, demonstrating effectiveness in the comprehensive treatment of HCC ( Lei et al, 2015 ; Chen et al, 2018 ; Zhou et al, 2018 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, berberine and curcumin are in phase I and II trials for treating ulcerative colitis and colorectal neoplasia, respectively [ 588 , 589 ]. Furthermore, National Medical Products Administration of China has approved icaritin for use in the treatment of hepatocellular carcinoma and ginsenoside RG3 has passed phase II clinical trials and is undergoing phase III clinical investigation for treatment of primary liver cancer [ 590 ]; however, the number of studies investigating the pharmacodynamics of herbal medicine remains limitedl. Further study of the roles of herbal medicine in influencing MYC, and quantitative data on their toxicity and bioavailability from human clinical trials, are urgently needed.…”
Section: Remarks and Further Perspectivesmentioning
confidence: 99%